Cost‐effectiveness analysis of sequential fecal microbiota transplantation for fulminant Clostridioides difficile infection. Issue 9 (17th March 2021) - Gupta, Sanchit; Zhu, Jinyi; McCarty, Thomas R; Pruce, Jordan; Kassam, Zain; Kelly, Colleen; Fischer, Monika; Allegretti, Jessica R
Abstract: Background and Aim: Fulminant Clostridioides difficile infections (FCDI) account for 8% of cases and substantial healthcare burden. Fecal microbiota transplantation is recommended for recurrent CDI, but emerging data support use for FCDI. We aimed to assess the cost‐effectiveness of a sequential fecal microbiota transplantation (sFMT) protocol for FCDI compared with current standard therapy. Methods: A Markov model simulated patients with FCDI in a 1‐year time horizon. The treatment algorithm for up to three sFMTs, clinical probabilities, and direct costs were used from published sources. Outcomes were quality‐adjusted life years (QALYs) and costs. The healthcare sector perspective was used with a willingness‐to‐pay threshold of 100 000 per QALY. Results: Sequential fecal microbiota transplantation (FMT) for FCDI was associated with lower overall cost (28 309 vs 33 980) and higher QALY (0.765 vs 0.686) compared with standard therapy. sFMT is cost‐effective in 100% of iterations. sFMT remained cost‐effective at cure rates > 44.8% for the first FMT and at stool preparation cost < 6944 per instillation. We find a wide range of efficacies for the first versus second FMT at which sFMT is still preferred. Value of information analysis estimates the expected value of perfect information to be low at 1.89 per person, quantified with net monetary benefit. Conclusions: An sFMT strategy strongly dominates standard therapy, with lower cost and higher QALY. Sensitivity analysis demonstrates benefit even if FMT cure rates are lower than expected and when multiple FMTs are required. FMT material in 2020 was priced at 1695 per treatment but remains cost‐effective at a much higher cost.